Automatic processing of natural-language electronic texts with NooJ : 10th International Conference, NooJ 2016, České Budějovice, Czech Republic, June 9-11, 2016, Revised selected papers /: 10th International Conference, NooJ 2016, České Budějovice, Czech Republic, June 9-11, 2016, Revised selected papers. (2016) - Unknown
No abstract available